DERADIKALISASI: UPAYA PEMERINTAH SEBAGAI PEMANGKU KEBIJAKAN DALAM MENJAGA PERDAMAIAN NEGARA MENURUT PERSEKTIF FIKIH JIHAD: DERADICALIZATION: GOVERNMENT EFFORTS AS POLICY MAKERS IN MAINTAINING COUNTRY PEACE ACCORDING TO THE PERSPECTIVE OF FIKIH JIHAD - Hasbi, Muhammad; Vijaini, Akhmad; Parahdina, Soraya; Maulida, Hilma (Mitsaqan Ghalizan, 2022)
Terrorism problem in Indonesia is one of the main problems that caught a serious attention from government. Series of a terror incidents so far show that there is a serious problem that has not solved yet to be fixed. Indonesia in the report of Global Terrorism Index (GTI) 2023 is ranked 24th from 163 countries that get most affected by terrorism with the total 638 incidents since 2000 until 2020. The terrorism action can endanger the security of nation and state. The consequence of that action are lost a life, a suspicion towards a particular race or religion, break up the nation's unity, damage physically and mentally, and raises fear in the society because the feel of threatened by the presence of terrorists. To deal with terrorism and radicalism, the government implements a program which known as deradicalization under National Counter Terrorism Agency (BNPT). With the deradicalization as the coaching program which aimed to change the terrorism convicts' radical character creates the expectation from public to the government in eradicating terrorism crime.